Resource productivity and economic wealth - Erich Hödl (Wirtschaft und Gesellschaft (WuG), 2017)
High economic growth in industrialised countries is questioned by growing ecological limits and the consumption-reducing effect of rising capital intensity of economic growth. Referring to the Europe 2020 Strategy it is shown by modern economic growth theory, that a vigorous rise of resource productivity by a resource-saving innovation system can assure high economic welfare without high economic growth. In the knowledge economy higher resource productivity will augment employment and wages without reducing the profit rate on the reduced capital stock. By augmenting resource and capital productivity more than labour productivity the productive system as the transformation instrument between nature and consumption can become smaller and depending on the desired level of consumption in industrial countries real capital exports to developing countries can augment.
Keywords: 330